Clinical characteristics and outcomes of EZH2-mutant myelodysplastic syndrome: A large single institution analysis of 1774 patients. (January 2023) - Ball, Somedeb; Aguirre, Luis E.; Jain, Akriti G.; Ali, Najla Al; Tinsley, Sara M.; Chan, Onyee; Kuykendall, Andrew T.; Sweet, Kendra; Lancet, Jeffrey E.; Sallman, David A.; Hussaini, Mohammad Omar; Padron, Eric; et al.
Abstract: EZH2 mutations in myeloid neoplasms are loss of function type, and have been linked to poor overall survival (OS) in patients with myelodysplastic syndrome (MDS). However, the specific determinants of outcomes in EZH2 -mutant (mut) MDS are not well characterized. In this single-center retrospective study, clinical and genomic data were collected on 1774 patients with MDS treated at Moffitt Cancer Center. In our cohort, 83 (4.7%) patients had a pathogenic EZH2 mutation. Patients with EZH2 mut MDS were older than EZH2 -wild type (wt) group (median age- 72 vs. 69 years, p = 0.010). The most common co-occurring mutation in EZH2 mut MDS was ASXL1, with a significantly higher frequency than EZH2 wt (54% vs. 19%, p < 0.001). Patients with EZH2 mut MDS had lower response rates to hypomethylating agents compared to EZH2 wt MDS (26% vs. 39%; p = 0.050). Median OS of patients with EZH2 mut MDS was 30.8 months, with a significantly worse OS than EZH2 wt group (35.5 vs. 61.2 months, p = 0.003) in the lower-risk IPSS-R categories. Among patients with EZH2 mut MDS, co-presence of ASXL1 or RUNX1 mutations was associated with inferior median OS compared to their wt counterparts (26.8 vs. 48.7 months, p = 0.031). Concurrent chromosome 7 abnormalities (12%) were also associated with significantly worse OS (median OS- 20.8 vs. 35.5 months, p = 0.002) in EZH2 mut MDS. Future clinical trials should explore the potential role of novel targeted therapies in improving outcomes in patients with EZH2 mut MDS. Highlights: Incidence of EZH2 mutation in MDS is 4.7%. EZH2 -mutant MDS commonly harbored concurrent deleterious ASXL1 and RUNX1 mutations. EZH2 mutation in MDS is associated with lower response rate to HMA. Presence of chromosome 7 abnormalities confer inferior OS in EZH2 -mutant MDS. EZH2 -mutant MDS had worse OS compared to wild type in patients with lower-risk MDS.